Giving new meaning to religious conversion: Churches, redevelopment, and secularization in Toronto. (5th November 2012) - Hackworth, Jason; Gullikson, Erin
<x xml:space="preserve">Abstract</x> Research on secularization has increased in recent years, particularly amongst urban geographers. Yet the debate is still dominated by competing theories that generally fail to account for the many institutions that impede and facilitate religiosity on the urban landscape. This article is about the role that land use planning regulations have had on changes to the religious landscape in Toronto. The empirical focus is on former churches that have recently been converted to residential uses. The larger conceptual goal is to explore the extent to which these transitions affect the religious landscape in the city and to determine what they can tell us about broader processes of secularization.